Exploring science 5 - Johnson, Penny; Levesley, Mark (Longman UK, 2004)
As part of our commitment to help you manage the transition between Key Stage 2 and 3, we have extended the course down into Years 5 and 6. Exploring Science 5 and 6 includes all the key features of the Key Stage 3 scheme.Matches the QCA Scheme of Work for upper Key Stage 2.Differentiated at three levels.Provides animations and pupils' activities on the interactive CD-Rom (for use on the school network or with an electronic whiteboard).Includes revision material for the Year 6 SATs, plus FREE SATs-style questions are provided on the companion website, www.exploringscience.co.uk.Includes investigation pages.Provides a post-SATs project Unit to help the transition to Year 7.